2016
DOI: 10.1021/acs.langmuir.6b01316
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Ceria–Platinum Inverse Catalyst for Partial Oxidation of Methanol

Abstract: Ceria-platinum-based bilayered thin films deposited by magnetron sputtering were developed and tested in regard to their catalytic activity for methanol oxidation by employing a temperature-programmed reaction (TPR) technique. The composition and structure of the samples were characterized by X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). Both conventional (oxide-supported metal nanoparticles [NPs]) and inverse configurations (metal with oxide overlayer) were analyzed to uncover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Reaction of methanol with oxygen can lead to the selective formation of formaldehyde 28 or the production of molecular hydrogen and carbon dioxide (CH 3 OH + 1/2O 2 → 2H 2 + CO 2 ). 99 Vanadia supported on ceria shows a remarkable activity for selective oxidation reactions. 100,101 The selective oxidation of methanol to formaldehyde was studied on a well-defined VO x /CeO 2 (111) model system for which the atomic surface structure has been determined.…”
Section: A Partial Oxidation Of Methanolmentioning
confidence: 99%
See 3 more Smart Citations
“…Reaction of methanol with oxygen can lead to the selective formation of formaldehyde 28 or the production of molecular hydrogen and carbon dioxide (CH 3 OH + 1/2O 2 → 2H 2 + CO 2 ). 99 Vanadia supported on ceria shows a remarkable activity for selective oxidation reactions. 100,101 The selective oxidation of methanol to formaldehyde was studied on a well-defined VO x /CeO 2 (111) model system for which the atomic surface structure has been determined.…”
Section: A Partial Oxidation Of Methanolmentioning
confidence: 99%
“…Temperature-programmed desorption at low vanadia loadings revealed reactivity at much lower temperature (310-430 K in Figure 18) as compared to pure ceria and vanadia on inert supports such as silica. 99 Calculations based on Density functional theory indicate that the special structural and electronic properties of VO 2 units dispersed on ceria facilitate the dehydrogenation of methanol (Figure 18). 99 At the origin of this support effect is the ability of ceria to stabilize reduced states by accommodating electrons in localized f-states.…”
Section: A Partial Oxidation Of Methanolmentioning
confidence: 99%
See 2 more Smart Citations
“…Another example of efficient inverse-catalyst system is offered by Pt-supported ceria, investigated as catalyst for methanol oxidation for clean hydrogen production. Ostroverkh et al 147 have shown that the performances of pure Pt surfaces are greatly enhanced when an ad-layer of ceria is adsorbed, ascribing the catalytic efficiency at the interface to the synergic contribution of the oxide in exchanging oxygen and of the metallic in anchoring the reactant species. Ceria on Ag particles has been proposed as a CO oxidation catalyst 148 , a system that exhibits also SERS resonant properties two orders of magnitude more pronounced than bare Ag particles.…”
Section: Have Investigated the Adsorption Of No Onmentioning
confidence: 99%